2019
DOI: 10.1111/joca.12265
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effectiveness of Financial Coaching: Evidence from the Boston Youth Credit Building Initiative

Abstract: Since the 2008 financial crisis, there has been renewed interest in providing financial education to improve consumer financial decision making, especially among youth. Using a randomized controlled trial, we estimate the causal effects of a financial coaching program for young adults from linked individual‐level administrative credit reports and self‐reported survey responses. Within six months, the treatment group was 10 percentage points more likely to have access to credit compared to the control group. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Some suggest that a step‐by‐step mastery experience may improve self‐efficacy (Asebedo, Seay, et al, 2019; Atlas et al, 2019; Lown et al, 2015) or that financial knowledge may be internalized and become FSE and financial behavior (Zhu & Chou, 2018). Locus of control is found to change with age (Kesavayuth et al, 2018), and several of the studies report that self‐efficacy may be increased by interventions, such as education, coaching, or socialization (Chan et al, 2017; Farrell et al, 2016; Loke et al, 2015; Magendans et al, 2017; Modestino et al, 2019; Rothwell & Wu, 2019; Skimmyhorn et al, 2016; Steinert et al, 2018). These findings are in line with Bandura's social cognitive theory and Rotter's social learning theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some suggest that a step‐by‐step mastery experience may improve self‐efficacy (Asebedo, Seay, et al, 2019; Atlas et al, 2019; Lown et al, 2015) or that financial knowledge may be internalized and become FSE and financial behavior (Zhu & Chou, 2018). Locus of control is found to change with age (Kesavayuth et al, 2018), and several of the studies report that self‐efficacy may be increased by interventions, such as education, coaching, or socialization (Chan et al, 2017; Farrell et al, 2016; Loke et al, 2015; Magendans et al, 2017; Modestino et al, 2019; Rothwell & Wu, 2019; Skimmyhorn et al, 2016; Steinert et al, 2018). These findings are in line with Bandura's social cognitive theory and Rotter's social learning theory.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies focus on financial vulnerability (Hoffmann & McNair, 2019), mastery beliefs (Asebedo, Seay, et al, 2019), or market volatility (Asebedo & Payne, 2019). A few studies specifically concern the effect of formal financial education or other financial training (Loke et al, 2015; Modestino et al, 2019; Rothwell & Wu, 2019; Skimmyhorn et al, 2016; Steinert et al, 2018; Zhu, 2019). Deenanath et al (2019) focus on socialization, including self‐efficacy, as an antecedent to financial behavior and knowledge.…”
Section: Synthesis and Analysismentioning
confidence: 99%
“…One large longitudinal study (Parks Opportunity Program (also called the "Assessing Financial Capability Outcomes Adult Pilot")) (Collins & Nafziger, 2019;Gons 2013;Wiedrich, Gons, Collins, & Drever, 2014) and five additional unrelated studies (Kim, Garman, & Sorhaindo, 2005;Moulton, Collins, Loibl, & Samek, 2015;Modestino, Sederberg, & Tuller, 2019;Roder, 2016& Theodos et al, 2016 reported on financial capability interventions related to adult financial education, counseling and coaching paired with a financial product. The interventions included pairing a low-cost transaction account or credit building loan product with financial counseling, coaching and education for adults.…”
Section: Adult Financial Education Counseling And/or Coaching Paired ...mentioning
confidence: 99%
“…While this may help close the gap in financial literacy across segments of the population, especially across racial/ethnic groups, it is debatable whether these programs have made a contribution in such direction. Some analyses have found that exposure to personal finance courses is associated with higher financial literacy and a lower probability and frequency of using AFS (Harvey, 2019; Kaiser et al, 2020; Modestino et al, 2019; Urban et al, 2015; Xiao & O'Neill, 2016). Other studies (Fernandes et al, 2014; Kassman et al, 2018) offer a more skeptical view about the effectiveness of state mandates.…”
Section: Literature Reviewmentioning
confidence: 99%